2001
DOI: 10.1183/09031936.01.00072001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEEP on inspiratory resistance in mechanically ventilated COPD patients

Abstract: This study aimed to investigate the effect of increased lung volume with positive end-expiratory pressure (PEEP) on respiratory resistance in patients with chronic obstructive pulmonary disease (COPD).Ten patients with COPD were mechanically ventilated for acute respiratory failure. PEEP was set at 0, 5, 10 and 15 cmH 2 O. Using the rapid airway occlusion technique, the total inspiratory resistance of the respiratory system was partitioned into interrupter (Rint,rs) and additional effective (DRrs) resistances.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The differences in parameter values between our study groups can also be attributed to different levels of hyperinflation, which may have been more serious in the AECOPD patients; however, in our study protocol, the premeasurement PEEP was standardized and the actual lung volumes were not known. We note that, although there is agreement between the results of Guerin et al (13) and those of the present study in regard to the decrease in R N , Guerin et al observed an unchanged viscoelastic behavior of the respiratory system with increasing PEEP. This is in sharp contrast with the decline in G with increasing PEEP in the present study, indicating that the two modeling approaches do not account for the combined effects of stress relaxation and ventilation inhomogeneity in a similar manner.…”
Section: Discussionsupporting
confidence: 91%
“…The differences in parameter values between our study groups can also be attributed to different levels of hyperinflation, which may have been more serious in the AECOPD patients; however, in our study protocol, the premeasurement PEEP was standardized and the actual lung volumes were not known. We note that, although there is agreement between the results of Guerin et al (13) and those of the present study in regard to the decrease in R N , Guerin et al observed an unchanged viscoelastic behavior of the respiratory system with increasing PEEP. This is in sharp contrast with the decline in G with increasing PEEP in the present study, indicating that the two modeling approaches do not account for the combined effects of stress relaxation and ventilation inhomogeneity in a similar manner.…”
Section: Discussionsupporting
confidence: 91%
“…This assumption may not be entirely valid in some cases [33,34]. However, continuous measurements of respiratory resistance are not typically available and the effect of this resistive term is limited mathematically in its impact.…”
Section: Discussionmentioning
confidence: 99%
“…No harmful effects have been reported from positive expiratory breathing (39). Although there have been some contradictory reports (37,39) and there have not yet been meta-analyses of the use of positive end-expiratory pressure for people with cystic fibrosis, chronic obstructive pulmonary disease or neuromuscular disorders, the majority of clinical studies (27,28,35,(40)(41)(42)(43)(44)(45) have described benefits of positive expiratory pressure on mucus clearance and pulmonary function.…”
Section: Effects Of Positive End-expiratory Pressure On Mucus Clearanmentioning
confidence: 99%